Conditions of Visibility: Contemporary Israeli Women's Cinema and Trauma in Michal Aviad's Invisible - Yosef, Raz (MiKAN, 2017)
The past decade has seen a renaissance of women's cinema in Israel. Through their films, a new generation of female filmmakers seek to redefine the conditions of representability of women in Israeli society and cinema. They shift the traditional place of the gaze and directly address the film spectator as a woman. Most of the current women's films deal with female trauma, which in itself is embedded in matters of visibility. Focusing mainly on Michal Aviad's 2011 film, Invisible, the article argues that the film seeks to question the position from which we view women's traumas. The film does not attempt to depict female suffering realistically, but rather to change the conditions of visibility of women's injury. It reflexively uses both documentary and fictional forms of representation, disrupting the coherent cinematic space and time and repositioning and restaging the gaze and the act of looking. Through this unique aesthetic, the film creates a critical distance for the viewer that enables a feminist political perspective, which may lead to a social change in representing the ongoing, insidious violent and oppressive reality that women experience in patriarchal society.